Pengaruh Budaya Organisasi dan Komunikasi Interpersonal Guru terhadap Manajemen Mutu Sekolah Taman Kanak-Kanak - Erni Kurniati (Jurnal Syntax Transformation, 2023)
School quality improvement management is a quality improvement method that is based on the school itself, applying a set of techniques, based on the availability of quantitative and qualitative data, and empowering all components of the school to continuously improve the capacity and organizational ability of the school to meet the needs of students and the community. This study aims to determine the influence of organizational culture and teacher interpersonal communication on the quality management of Kindergarten schools in the Tangerang District. This study uses a descriptive quantitative approach. The variables in this study are Organizational Culture, Interpersonal Communication and Quality Management. The population in this study were 222 teachers in the Tangerang District from 37 Kindergartens. Sampling used a random sampling technique and obtained a sample of 143 teachers and 30 teachers as a trial. Data collection is done by questionnaire. Validity test using product moment correlation and reliability using alpha cronbach. The results of the study obtained the following conclusions: 1) There is a positive and significant influence of Organizational Culture on the Quality Management of Kindergarten Schools in Tangerang District, Tangerang City, with an r count value of 0.559, β value = 0.580 and t value = 8.001 with a smaller significant value of 0.000 from 0.05. 2) There is a positive and significant influence of Interpersonal Communication on the Quality Management of Kindergarten Schools in Tangerang District, Tangerang City, with a t-value of 11.822 with a significant value of 0.000 which is less than 0.05, the value of r = 0.706 and β = 0.706. 3) There is a positive and significant influence of Organizational Culture on Interpersonal Communication of Kindergarten Teachers in Tangerang District, Tangerang City, with a t-value of 6.045 with a significant value of 0.000 which is less than 0.05, the value of r and β = 0.454